2007
DOI: 10.1007/s12011-007-8021-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Selenium on Nicotine-Induced Testicular Toxicity in Rats

Abstract: Effect of exogenous selenium at a dose of 10 mug/kg body weight on the testicular toxicity induced by nicotine in rats was investigated. Male albino rats were maintained for 60 days as follows: (1) control group (normal diet), (2) nicotine group (0.6 mg /kg body weight), (3) selenium (10 microg/kg body weight), and (4) nicotine (0.6 mg/kg body weight) + selenium (10 microg/ kg body weight). Administration of nicotine caused reduction in sperm count and sperm motility. Activity of HMG CoA reductase and concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
21
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 20 publications
11
21
0
2
Order By: Relevance
“…Previous studies in our lab also supported these results [8]. In the group administered selenium along with nicotine, a very low amount of cotinine, a major metabolite of nicotine, was detected, whereas nicotine was not detected.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies in our lab also supported these results [8]. In the group administered selenium along with nicotine, a very low amount of cotinine, a major metabolite of nicotine, was detected, whereas nicotine was not detected.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies in our laboratory have shown that selenium administration reduces alcohol-and nicotine-induced toxicity in the testis [7,8]. We have also studied the impact of high and low doses of selenium on nicotine-induced hyperlipidemia in experimental rats, and our studies confirmed that coadministration of selenium at a dose of 1 μ/100 g body wt and nicotine offers protection against nicotine-induced hyperlipidemia [9].…”
Section: Introductionsupporting
confidence: 77%
“…Indeed, oxidative stress may be a concurrent mechanism of NT testicular toxicity. Nicotine increases ROS by breaking the mitochondrial respiratory chain (Guan et al, 2003) and inhibits testosterone biosynthesis in mouse Leydig cells (Patterson et al, 1990); the NT-enhanced ROS production impairs steroidogenesis at the first step of cholesterol transfer to the mitochondria by suppressing the steroidogenic acute regulatory (StAR) protein expression (Jana et al, 2010;Seema et al, 2007). Spermatozoa, being rich in polyunsaturated fatty acids, are liable to lipid peroxidation by ROS that will result in changes of membrane structural integrity and fluidity.…”
Section: Tablementioning
confidence: 99%
“…Levels of testosterone in the serum were also reduced. However, the extent of these alterations was lesser in the group administered with nicotine along with selenium [33]. Yu et al [34] concluded that 0.1 mg/kg selenium(Na 2 SeO 3 ) inhibited oxidative stress, apoptosis and cell cycle changes induced by excess fluoride in kidney of rats.…”
Section: Figurementioning
confidence: 99%